2021
DOI: 10.4038/sljer.v8i2.140
|View full text |Cite
|
Sign up to set email alerts
|

Productivity of Agri-Food Sector of Sri Lanka: The Story Unseen, Unfolded or Untold

Abstract: The agriculture sector in Sri Lanka has been perceived by a large proportion of politicians, policy makers, scientists, academia, and general public as a sector with "low productivity". Yet, once the contribution of food and related industries are added, the Agri-Food Sector (AFS) is highly productive and vibrant, just as much as in any economy. Therefore, the political leadership should be aware of the contributions made by the AFS and be cautious in interpreting the productivity estimates made by various age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The accuracies of each can be viewed in the below table. When comparing this research with previous studies, it is evident that although previous studies [5][6] [13] have identified issues in the fertilizer subsidy program, none of them has proposed an implementation to effectively distribute the subsidy among farmers, taking into account the urgency of their needs. This research addresses this gap and provides a method to conveniently distribute the fertilizer subsidy to farmers, ensuring the timely application of fertilizers to their fields.…”
Section: Priority-based Fertilizer Subsidy Distributionmentioning
confidence: 96%
See 2 more Smart Citations
“…The accuracies of each can be viewed in the below table. When comparing this research with previous studies, it is evident that although previous studies [5][6] [13] have identified issues in the fertilizer subsidy program, none of them has proposed an implementation to effectively distribute the subsidy among farmers, taking into account the urgency of their needs. This research addresses this gap and provides a method to conveniently distribute the fertilizer subsidy to farmers, ensuring the timely application of fertilizers to their fields.…”
Section: Priority-based Fertilizer Subsidy Distributionmentioning
confidence: 96%
“…The study recommended a phased-out subsidy scheme, accompanied by infrastructure investments and improved marketing efficiency, for long-term productivity. Additionally, an analysis [13] demonstrated the positive effects of fertilizer use on paddy production in Sri Lanka, underscoring the significance of sustainable fertilizer policies given domestic and international market implications. It emphasized the need to evaluate experimental policies related to land, fertilizer, and inputs over time.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation